Komuniksi Dakwah Interpersonal Antara Peruqyah Dengan Pasien Di Klinik Al-Hijrah Kota Palembang - Ramadhani Karimah; Achmad Syarifudin; Modh Aji Isnaini (CV. ITTC INDONESIA, 2023)
: This research is about Interpersonal Da’wah Communication between Peruqyah and Patients at the Al-Hijrah Clinic Palembang City. Interpersonal communication plays an important role in the delivery of islamic da’wah. One of the delivery of islamic da’wah can be done with the ruqyah process. The purpose of this research is to find out how the interpersonal communication aspects are contained in the ruqyah process. This study uses a qualitative research method, where the data obtaine emphasizes words and pictures. Data collection techniques include observation, interviews, and documentation. The results of this study can be seen that aspects of interpersonal communication play an important role in the ruqyah process so that the message of islamic da’wah is conveyed. With the interpersonal communication carried out by Ustadz Parto to his patients, patients can receive messages easily.